(untitled) (Journal of the Bangladesh Agricultural University, 2024)
An in vivo study was conducted with various cooking recipes to select suitable wheat flour in view point of glycemic index (GI) value from the commercially available whole and plain wheat flour by comparing with natural wheat flour. We assessed the glycemic responses of 10 healthy individuals with reference food (50 g glucose) and cooked wheat roti, equivalent to 50 g carbohydrate, in hot (100°C) and normal water (25°C) recipes. To prevent residual effects, the individuals were kept overnight fasting throughout the study period. Capillary glucose levels at 0, 15, 30, 45, 60, 90 and 120 minutes after consuming the meals were assessed and used to determine the Incremental Area Under Curve (IAUC). Results showed a significant decrease (p<0.001 and p<0.005) in glucose levels of the test foods compared to reference food. The measured GI values of the samples processed with normal water were categorized as low (plain wheat flour, 52), medium (56 for whole wheat flour) and high (natural flour, 73). But all the samples were in low GI class when processed with hot water; GI was 43, 47 and 44 for whole wheat flour, plain wheat flour, and natural wheat flour, respectively. The temperature differences in the recipes are believed to be the primary cause of variation in GI. Hot water treatment provided low GI in the recipes that may be good for both healthy and diabetic people. J Bangladesh Agril Univ 22(2): 257-266, 2024